Meningkatkan Kemampuan Berpikir Kritis Dan Pengambilan Keputusan Peserta Didik Melalui Penggunaan Model Group Investigation Pada Materi Stoikiometri Pokok Bahasan Konsep Mol Kelas X MIA Sma Muhammadiyah 2 Banjarmasin : Indonesia - Aditya Saputra, Muhammad; Hamid, Abdul; Winarti, Atiek; Aufa, Mohamad Nor; Hasbie, Muhammad; Fitri, Muhammad Awaluddin (LPPM Universitas Negeri Jakarta, 2023)
Research has been conducted using the Group Investigation model of mole concept material. The aim of this study used to enhance critical thinking and decision making about the concept material of the mole. The subjects of the study were 32 high school students at Muhammadiyah 2 Banjarmasin in X grade Mathematics and Natural Sciences School Year 2018/2019. Research using test and non-test instruments. Research that resulted in increased aspects of the attitude of students increased from the good enough category with a score of 8.14 to a good category with a score of 11.52, the skills of students increased from the category of quite skilled with a score of 8.15 being skilled with a score of 10.82, critical thinking learners from the indicators (1) examine the questions (2) decide on actions (3) weigh the researcher's report and induce a quite critical category with an average score of 54.28 increasing to 62.76 and categorized as critical, and learning outcomes aspects of students' knowledge from completeness 65.73% to 75.94, as well as students' decision making from indicators 1) predicting risk 2) identifying choices 3) analyzing information 4) determining choices increasing from category quite well with an average score of 39.71 becoming 51, 17 and categorized as good